DINAMISASI DAN ELASTISITAS HUKUM KEWARISAN ISLAM - Komari Komari (Jurnal Hukum dan Peradilan, 2012)
Islamic law of inheritance is, to be followed by all Muslims, but its implementation is not in accordance with the provisions of Islamic law, this is caused by lack of understanding of Islamic inheritance law. In the application of the Islamic law of inheritance can be different from the norms of Islamic law itself, which is done by reconciliation or peace, which is not in accordance with the provisions of Islamic law, but through the application of such a method of interpretation. Interpretation in the application of the law of inheritance is possible in an understanding of the heirs any other alternative that contains the values of justice and peace among the heirs and families. Keywords: Dynamics, Elestisitas, Islamic inheritance law